Display life and related traits of low-dose irradiated, boneless, pork chops - S E Luchsinger; Zepeda C.M. Garcia; Edgar IV Chambers; M E Hollingsworth; Melvin C Hunt; James L Marsden; Sally L Stroda; Canas E Rubio J; Curtis L Kastner; W G Kuecker; T Mata; Donald H Kropf (Kansas Agricultural Experiment Station Research Reports, 1995)
Irradiation and vacuum-packaging caused a more intense and stable red color in boneless pork chops. Irradiation up to 2.5 kGy increased cooked internal redness in chilled chops. Oxidative rancidity was greater in aerobic packaging than vacuum-packaging and in irradiated aerobic packaged chops than controls. Irradiation of vacuum-packaged boneless pork chops has promising potential for market acceptance.; Swine Day, Manhattan, KS, November 16, 1995
Keywords: Swine day; 1995; Kansas Agricultural Experiment Station contribution; no. 96-140-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 746; Swine; Irradiation; Color; Oxidation